The People’s Game: Uncovering Diversity in Baseball, Pottawatomie County and Humboldt, Kansas, 1911-1924 - Combes, McKenzie (Kansas State University, The Chapman Center for Rural Studies, 2018)
This is a study of baseball in the early twentieth century and the diversity within town teams in Kansas. Research reveals that several Kansas towns housed African-American and women’s teams. This paper is based on fieldwork, journals, books, and historical newspapers and photographs.
McKenzie Combes, “The People’s Game: Uncovering Diversity in Baseball, Pottawatomie County and Humboldt, Kansas, 1911-1924,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/255.
Keywords: African American history; baseball; Kansas City Monarchs; Pottawatomie County; Wamego; Women's baseball